Kualitas tidur dan tekanan darah pada supir bus lintas Sumatera: Studi pada trayek Banda Aceh - Medan - Maulida, Dara; Lubis, Halinda Sari (TROPHICO: Tropical Public Health J., 2023)
A changes in blood pressure is affected by different types of work. Driver can be detected an increase in hypertension due to fatigue of physical activity , stress of work pressure, environment and lifestyle. Fatigue and stress due to work pressure distrupt sleep patterns, resulting disturbingÂ  sleep performance especially bus drivers operates at night need high alertness. This study aims for identifying sleep quality with blood pressure in bus drivers across Sumatera on the Banda Aceh-Medan route with a descriptive design and 30 participant as samples. The results showed that most drivers experienced poor sleep quality with normal blood pressure. The recommended that the bus entrepreneur strives driverâ€™s physical fitness to obtain a good sleep quality.